Najpiękniejszy człowiek pokolenia. Świętego Brata Alberta (i Jakuba A. Malika) „pozytywizm ewangeliczny”? Garść uwag - Karpowicz-Słowikowska, Sylwia (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Adam Chmielowski (Saint Brother Albert) by Jakub A. Malik, and previously, Adolf Nowaczyński was interpreted as the materialization of the “evangelical positivist” model. The term, coined by Adam Grzymała-Siedlecki for the study of BolesławPrus, became not only a term which, in literary science, repeatedly served as a formula for positivists’ views on religion, but also turned out to be a knot for research interests of Malik, a knot connecting it in a broadly understood humanistic perspective with with Stanisław Fita and the author of the novel The doll.